Maritime Building, New York World's Fair 1939 (Grinnell Litho Co.)
The twin ship prows which flank the main entrance of this building provide an imposing background for exhibits of the latest types and techniques of marine transportation. This nautical atmosphere has also been very effectively in the decoration of the exhibit hall, which contains educational displays of marine transportation.